2015
DOI: 10.1002/wsbm.1321
|View full text |Cite
|
Sign up to set email alerts
|

In search for symmetries in the metabolism of cancer

Abstract: Even though aerobic glycolysis, or the Warburg effect, is arguably the most common trait of metabolic reprogramming in cancer, it is unobserved in certain tumor types. Systems biology advocates a global view on metabolism to dissect which traits are consistently reprogrammed in cancer, and hence likely to constitute an obligate step for the evolution of cancer cells. We refer to such traits as symmetric. Here, we review early systems biology studies that attempted to reveal symmetric traits in the metabolic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…We and others previously found that distinct cancer types featured few common gene-expression changes in metabolism from their respective non-cancerous tissues, which were primarily ascribed to altered nucleotide biosynthesis (Gatto et al, 2014;Hu et al, 2013;Nilsson et al, 2014). However, these studies could not distinguish whether the observed changes in gene expression are attributable to a common adaptation process during cancer progression or are rather the consequence of a specific mutation event (Gatto and Nielsen, 2016). To determine this, we selected among the genes found to be associated with nine mutated genes those that overlap with the 3,765 genes that participate in the human metabolic network (Mardinoglu et al, 2014).…”
Section: Mutation-associated Gene-expression Changesmentioning
confidence: 83%
“…We and others previously found that distinct cancer types featured few common gene-expression changes in metabolism from their respective non-cancerous tissues, which were primarily ascribed to altered nucleotide biosynthesis (Gatto et al, 2014;Hu et al, 2013;Nilsson et al, 2014). However, these studies could not distinguish whether the observed changes in gene expression are attributable to a common adaptation process during cancer progression or are rather the consequence of a specific mutation event (Gatto and Nielsen, 2016). To determine this, we selected among the genes found to be associated with nine mutated genes those that overlap with the 3,765 genes that participate in the human metabolic network (Mardinoglu et al, 2014).…”
Section: Mutation-associated Gene-expression Changesmentioning
confidence: 83%
“…It includes not only alterations in lipid metabolism but also elevation in glycolysis, glutaminolytic flux, amino acid metabolism, mitochondria biogenesis and pentose phosphate pathway. Although it is a phenomenon resulting from oncogenic mutations, the metabolic switch observed in the majority of cancer types seems to be context-dependent, namely, largely attributable to the microenvironment, rather than specific to the particular type of malignancy [ 85 , 86 ]. An interest notion that emerged in recent years is that most cancer samples retain a substantial similarity with the tissue of origin regarding the expression of metabolic genes.…”
Section: Metabolic Changes In Cancer Developmentmentioning
confidence: 99%
“…For instance, cancer specific GEMs together with EA and SLA analysis were recently used for identification of oncogenes/metabolites and biomarkers for diagnosing specific cancer (Agren et al, 2014 ; Jerby-Arnon et al, 2014 ; Gatto et al, 2015 ; Gatto and Nielsen, 2015 ). Since this procedure mainly uses the true-negative part of EA and SLA, the analysis could be highly reliable.…”
Section: Using Gems In Studies Of Systems Medicinementioning
confidence: 99%